The Level of Knowledge, Motivation, and Self Efficacy of Post-Stroke Patients in Lumajang - Atikah Fatmawati; Fendik Pradana (STIKes Patria Husada Blitar, 2021)
Post-stroke conditions can be stressful and unpredictable. Knowledge, motivation, and self-efficacy are essential to the long-term care of post-stroke patients. This study aimed to analyze the correlation between the level of knowledge, motivation, and self-efficacy of post-stroke patients in Lumajang. This study used a cross-sectional design. The population of this study was post-stroke patients in Lumajang. The sampling technique used consecutive sampling with the number of samples obtained, namely 55 samples. The variables of this study were the level of knowledge, motivation, and self-efficacy. The data collection was carried out by using a questionnaire. The data analysis was performed by using the Spearman Rank test. The results showed a correlation between knowledge and motivation with self-efficacy in post-stroke patients, with p-values of 0.004 (r: 0.383) and 0.000 (r: 0.581). A person who had high knowledge and motivation would show positive results in managing his disease; for example, in the stroke concept, the patient will actively participate in the rehabilitation program, treatment program, and schedule visits to health care facilities.